Habit Watching Movie With English Subtitles as an Alternative in Improving on Students' Reading Skill - Nadivah Nadivah; Suryadi Suryadi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The objective of this study is to establish a correlation between the practice of watching English language films and the utilization of English subtitles as a substitute method to enhance students' English reading comprehension. The research was carried out at SMA Negeri 1 Tirtayasa. This study seeks to ascertain the extent to which students' comprehension improves by regularly watching English films with subtitles. The employed methodology is quantitative, focusing on a population of students in classes XII Science 1, 2, 3, and 4. Subsequently, a total of 76 students were included in the sample. The collected data pertains to the English reading comprehension test of the students. The independent variable in this study refers to the practice of watching English films with English subtitles, whereas the dependent variable pertains to the English reading comprehension skills of the students. The investigation yielded substantial data. The term